Hydrogels Used As A Potential Drug Delivery System: A Review - Kumar, Manish (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Hydrogels, the swellable polymeric materials have been widely investigated as the carrier for drug delivery systems. These biomaterials have gained attention owing to their peculiar characteristics like swelling in aqueous medium, pH and temperature sensitivity or sensitivity towards other stimuli. Hydrogels being biocompatible materials have been recognized to function as drug protectors, especially for peptides and proteins, from in-vivo environment. Also, these swollen polymers are helpful as targetable carriers for bioactive drugs with tissue specificity. Hydrogels are presently under investigation as a delivery system for bioactive molecules, because of their similar physical properties as that of living tissue, which is due to their high water content, soft and rubbery consistency, and low interfacial tension with water or biological fluids. This review presents an overview to the advances in hydrogel based drug delivery that have became the interest of most researchers.